Group 5 imido complexes derived from diamido-pyridine ligands. - Pugh, S; Blake, A; Gade, L; Mountford, P (2001)
Reaction of the vanadium(V) imide [V(NAr)Cl(3)(THF)] (Ar = 2,6-C(6)H(3)(i)()Pr(2)) with the diamino-pyridine derivative MeC(2-C(5)H(4)N)(CH(2)NHSiMe(2)(t)()Bu)(2) (abbreviated as H(2)N'(2)N(py)) gave modest yields of the vanadium(IV) species [V(NAr)(H(3)N'N' 'N(py))Cl(2)] (1 where H(3)N'N' 'N(py) = MeC(2- C(5)H(4)N)(CH(2)NH(2))(CH(2)NHSiMe(2)(t)()Bu) in which the original H(2)N'(2)N(py) has effectively lost SiMe(2)(t)()Bu (as ClSiMe(2)(t)()Bu) and gained an H atom. Better behaved reactions were found between the heavier Group 5 metal complexes [M(NR)Cl(3)(py)(2)] (M = Nb or Ta, R = (t)()Bu or Ar) and the dilithium salt Li(2)[N(2)N(py)] (where H(2)N(2)N(py) = MeC(2-C(5)H(4)N)(CH(2)NHSiMe(3))(2)), and these yielded the six-coordinate M(V) complexes [M(NR)Cl(N(2)N(py))(py)] (M = Nb, R = (t)()Bu 2; M = Ta, R = (t)()Bu 3 or Ar 4). The compounds 2-4 are fluxional in solution and undergo dynamic exchange processes via the corresponding five-coordinate homologues [M(NR)Cl(N(2)N(py))]. Activation parameters are reported for the complexes 2 and 3. In the case of 2, high vacuum tube sublimation afforded modest quantities of [Nb(N(t)()Bu)Cl(N(2)N(py))] (5). The X-ray crystal structures of the four compounds 1, 2, 3, and 4 are reported.